PEMANFAATAN KOTORAN BABI MELALUI KOMPOSTING DAN PENGARUHNYA TERHADAP PERTUMBUHAN LOMBOK RAWIT (CAPSICUM FRUTESCENS) - Budiarsa Suyasa, I W.; Kunti Sri Panca Dewi, I G.A (Bumi Lestari; Vol 8 No 1 (2008))
The research was conducted about dirt pig compost with variation of composition, Toksicity of it was detected by influence to Growth Of Lombok Rawit ( Capsicum Frutescens). The composition of it is I ( pig dirt 40%, hay 40%, dregs know 18%, dolomit 20%), II ( pig dirt 60%, hay 22%, dregs know 13%, dolomit 2%), and III ( pig dirt 70%, hay 13%, dregs know 15%, dolomit 2%). Growth of microorganism in compost process cover two phase that is ferment phase and maturation Process of composting with composition of III ( pig dirt 70%, hay 13%, dregs know 15%, dolomit 2%) owning best quality. That shown from speed of maturation time posed at stability of temperature and pH reached at period six week, influence to growth of lombok rawit ( Capsicum Frutescens) tried give best level of growth that seen amount of leaf more than composition I and II.
Keywords: Composition, composting and growth of crop